Evaluation of anxiety levels of pregnant women with gestational diabetes mellitus - Güler, Aşkın Evren; Demirel Güler, Zeliha Çiğdem; Budak, Asil; Koparal, Buket; Şehirli Kıncı, Özge (Perinatal Medicine Foundation, 2020)
Objective The aim of this study was to investigate the anxiety levels of pregnant women with gestational diabetes mellitus (GDM) followed by different treatment methods. Methods Our study was carried out with 141 cases whose pregnancy follow ups were made in Gynecology and Obstetrics Clinic. Cases which had GDM screening with 75-g oral glucose tolerance test (OGTT) were divided into 3 groups. Group 1 (control group) consisted of 50 cases with 75-g OGTT results in normal range, Group 2 consisted of 50 cases which had significant 75-g OGTT results and followed up by diet (A1), and Group 3 consisted of 41 cases which were diagnosed with GDM as a result of 75-g OGTT and received diet as well as medical therapy (A2). Beck anxiety inventory (BAI) was administered to the patients in Group 1 in 24th week, and to patients in Groups 2 and 3 in the 24th and 32nd weeks. Results In the first evaluation of the patients, BAI scores of the control group were statistically found to be significantly lower than the patients with GDM (p=0.001). There was no significant difference in BAI scores among patients diagnosed with GDM, and high anxiety scores were found in both groups. There was a significant decrease in anxiety levels in the Groups 2 and 3 after the treatment (p<0.01). In the Group 2, the BAI scores were observed to decrease from 51.76±4.47 to 45.62±3.65, and from 51.73±5.27 to 41.48±3.29 in the Group 3 (p<0.001). Conclusion In addition to the metabolic disorders brought by the disease itself, GDM can cause various problems by increasing the levels of anxiety in patients. With an effective treatment for glycemic control, anxiety levels of patients can be reduced.